Human activity recognition based on ELM using depth Images / \c Ahmed Kawther Hussein Al-Saffar - Hussein, Ahmed Kawther (School of Computer and Communication Engineering, Universiti Malaysia Perlis, 2017)
This research aims at achieving certain objectives which are as follows ; to develop a scalable scheme for feature development in HAR system ; to develop an optimization scheme of Extreme Learning Machine (ELM) algorithm for classification purposes ; to evaluate the developed schemes and algorithms using standard benchmark data.